Global rise in gender-based violence against women and girls during COVID-19 lockdown: An insight from Africa - Linus Oluchukwu Akudolu; Charles N. Okolie; Edward Ajanwachukwu Okoro; Bright E. Nwamuo; Ifeanyi Okeke; Stephen Aigbonoga; Vitalis C. Ugwu; Ernest Osuchukwu; Vincent Anyika; Esther Ogbu (Cogent Arts & Humanities, 2023)
One of the negative impacts of COVID-19 lockdown was a drastic global increase in gender-based violence against women and girls. Therefore, this paper is an investigation on gender-based violence against women and girls during the lockdown, its causes, ethical implications and recommendations, with insights from African nations. The paper condemns gender-based violence as unethical as it violates the principle of human dignity. Recommendations on how to curb the menace both at sundry and pandemic period are nonetheless made. The work is qualitative research sourcing its data from library materials, reported cases and interviews. All the data collected in the course of this study are interpreted with the application of hermeneutics, critical analysis and logical reasoning.